Tinjauan Hukum Positif dan Hukum Islam terhadap Praktik Pinjaman Keuangan Informal (Bank Keliling) - Muhammad Zia Ul Haaq; Fikrotul Jadidah (PT Elaborium Elevasi Indonesia, 2026)
This study analyzes the practice of mobile bank lending through the lens of positive law and Islamic law while examining its socio-economic implications for local communities. This study aims to educate the public about informal financial lending practices, and to analyze the factors contributing to their emergence and impacts (socio-economics), in order to promote more equitable to economic practices that are consistent with the principles of Islamic jurisprudence (fiqh). The research methodology combines a normative–empirical approach with juridical analysis, complemented by a literature review approach. This informal financing mechanism has expanded due to the demand for rapid access to funds without complex administrative requirements. However, it raises substantial legal concerns, as such activities typically operate without authorization or oversight from the Financial Services Authority or Bank Indonesia, thereby violating the provisions of Law No. 10 of 1998 on Banking and potentially giving rise to civil and criminal liabilities. From the perspective of Islamic law, this practice is deemed invalid due to the presence of riba, gharar, and elements of injustice that contradict the principles of maqāṣid al-sharī‘ah. Socio-economically, mobile bank lending generates adverse impacts on community welfare, including excessive interest burdens, debt dependency, and declining productivity caused by financial and psychological pressures. The study concludes that enhanced regulatory enforcement, improved financial literacy, and the strengthening of formal microfinance institutions—including Sharia-based financing—are essential to mitigating negative outcomes and providing safer and more equitable financing alternatives.